DENTEX: The emergence of dental therapists in the United States. Issue 4 (April 2016) - Fiset, Louis
Abstract : ABSTRACT: Dental therapists were introduced into Alaska in 2005 to meet the basic oral health needs of Alaska Native communities. Deployed in 54 countries, dental therapists are well distributed throughout their respective societies. In Alaska, they provide effective, quality, and safe care for children in an economical manner and are generally accepted both by the public and by the dental profession. Dental therapists are increasingly employed in other states. Historical parallels exist between the physician assistant movement and dental therapists in the United States.